Entscheidungsprobleme bei Kleinkrediten am Beispiel des Pfandkredits - Friedrich Thießen (Kredit und Kapital, 2006)
Mit der Neuordnung der Verbraucherkreditregulierung durch die EU (Verbraucherkreditrichtlinie) und einer Zunahme von Armutskrediten ("sub prime lending") in einigen Industrieländern ist die Frage aufgetaucht, welche Kalküle bei Entscheidungen über Kleinkredite zum Tragen kommen. In vielen Ländern gibt es eine Tradition, Kleinkredite von Verbraucherkreditregulierungen auszunehmen, u.a. weil die Risiken für "überschaubar" und die Pflichten für "einschätzbar" gehalten werden. Empirisch zeigt sich, dass Kleinkreditnehmer häufig Entscheidungen treffen, die mit – relativ und absolut – sehr hohen finanziellen Belastungen verbunden sind. Am Beispiel des Pfandkredits kann gezeigt werden, welches Ausmaß diese Kosten annehmen können und wie die Entscheidungskalküle beschaffen sind. Es ergibt sich, dass der Pfandkredit Eigenschaften von schwierig zu beurteilenden Derivaten (Optionen) besitzt. In Verbindung mit bekannten Verhaltensanomalien aus der Behavioral-Finance-Lehre können die zu beobachtenden Verhaltensweisen der Kreditnehmer erklärt werden. Die Überlegungen können auf andere Kredittypen übertragen werden. (JEL D14, G21, I39)) – – Decision-making Problems in Small-scale Lendings for Personal Use Demonstrated by the Example of Pawn Credit Should Loans for Personal Use not be Subject to Consumer Credit Protection Rules? The Special Decision-making Logic Inherent in Small-scale Lendings for Personal Use such as Pawn Credits As a result of EU activities aimed at modifying rules on consumer protection in the field of lending (modification of Consumer Credit Directive) and of sub-prime lending on an increasing scale in a number of industrial countries, the question has arisen about the considerations playing a role when decisions are made on small-scale lendings for personal use. It has been a tradition of many countries to exempt small-scale lendings for personal use from the scope of application of consumer credit regulations, because risks are deemed to be "manageable in terms of amount" and obligations to be "foreseeable", inter alia. Empirical evidence has shown, however, that individuals seeking to obtain small-scale loans often make decisions resulting in extremely high financial burdens in both relative and absolute terms. Pawn credits have been used as an example in order for showing the dimensions such loans may potentially have as well as the quality of the reasons guiding decision-making. It has turned out that pawn credits have properties of derivative instruments that are difficult to assess. In connection with behavioural norms known from the science of behavioural finance it is possible to explain borrowers' modes of behaviour. These considerations may also be applied to other types of credit.
Keywords: D14; G21; I39; 330